2014
DOI: 10.1111/cyt.12220
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical staining for stratifin and OCIAD2 in bronchial washing specimens increases sensitivity for diagnosis of lung cancer

Abstract: Immunocytochemical staining for stratifin and OCIAD2 improved diagnostic sensitivity for lung cancers but diagnostic specificity was lower than that for cytology alone. The immunostains carried up to a 10% risk of a false-positive result and therefore positive staining must be confirmed by morphological evidence of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…For example, some studies found that SFN could facilitate progression and development of lung adenocarcinoma at an early stage [7]. Besides, combined with OCIAD2, immunocytochemical staining for SFN could also enhance diagnostic sensitivity for lung cancers [8]. For breast cancer, it is determined that the biology of SFN is important in cellular movement and is contingent on breast cancer subtype [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies found that SFN could facilitate progression and development of lung adenocarcinoma at an early stage [7]. Besides, combined with OCIAD2, immunocytochemical staining for SFN could also enhance diagnostic sensitivity for lung cancers [8]. For breast cancer, it is determined that the biology of SFN is important in cellular movement and is contingent on breast cancer subtype [9].…”
Section: Introductionmentioning
confidence: 99%
“…We have extensively studied the gene expression profiles of early stage adenocarcinoma and found several genes that are overexpressed in early invasive tumors but not in adenocarcinoma in situ . These genes include stratifin (SFN) [9], immunoglobulin binding protein 1 (IGBP1), [10] ovarian carcinoma immunoreactive antigen domain 2 (OCIAD2), [11] and dimethylarginine dimethylaminohydrolase 2 (DDAH2) [12]. In the course of our investigations, we realized that overexpression of all these genes does not occur through genetic alteration but is associated with epigenetic abnormality.…”
Section: Introductionmentioning
confidence: 99%
“…OCIAD1 and OCIAD2 are human cancer-related proteins implicated in ovarian 1 , thyroid 2 and lung cancers 3 , and in various hematological neoplasms 4 , 5 including multiple myeloma 6 and neutrophilia 7 . Their names derive from the first report on OCIAD1 (Ovarian Carcinoma Immunoreactive Antigen domain-containing protein 1), which was found in ascites fluid of patients with metastatic ovarian cancer and mapped to chromosome 4p11 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Although OCIAD2 expression varies among different cancers, its precise function remains unknown - while high levels of OCIAD2 are reported in ovarian mucinous tumors 1 and lung carcinomas 3 , 13 ; significantly reduced OCIAD2 expression is reported in liver and gastric carcinomas 14 , glioblastomas 15 and chronic lymphocytic leukemia 16 . Further, loss of OCIAD2 function promotes cancer progression by increasing activation of the PI3K/Akt pathway 17 .…”
Section: Introductionmentioning
confidence: 99%